Numerical Analysis of Radiative Recombination and Reabsorption in GaAs/Si Tandem - Ren, Zekun; Mailoa, Jonathan P.; Liu, Zhe; Liu, Haohui; Siah, Sin Cheng; Buonassisi, Tonio; Peters, Ian Marius (IEEE Journal of Photovoltaics, 2015)
We demonstrate a numerical analysis of the device impact of photon reabsorption on single-junction GaAs and tandem GaAs/Si solar cells. A self-consistent optical-electrical model that considers nonideal losses within the devices is developed. For single-junction devices, we find that the impact of photon recycling on the voltage increases monotonically with the injection level. For record-level GaAs solar cells, the voltage boost is 33 mV under open-circuit conditions and 13 mV at the maximum power point. For tandem GaAs/Si solar cells, photon reabsorption moderates the sensitivity of tandem efficiency to both obvious parameters like absorber thickness and implicit parameters like shunt resistance (Rsh) and bulk lifetime. Considering luminescent coupling results in a GaAs top cell that is 9.5% thicker than without luminescent coupling. The tandem device is 50% more sensitive to R-sh changes in the GaAs cell than R-sh changes in the Si cell. The impact of the GaAs top-cell bulk lifetime on tandem efficiency is reduced by 61% if photon reabsorption is not considered. This integrated optoelectronic device model allows one quantification of the implicit effects of photon recycling and luminescent coupling on device parameters for GaAs/Si tandem, providing a valuable tool for high-performance device optimization.
CRIS-Team Scopus Importer:2023-03-07
Keywords: III-V solar cell; Luminescent coupling (LC); photon recycling (PR); Si solar cell